Spinal Epidermoid Cyst in a Child- An Experience with a Rare Case - Chaudhary, P; Shrestha, BP; Khanal, GK; Maharjan, R; Kalawar, RPS; Pokharel, B; Limbu, A; Baral, P; Shah, AB; Mishra, D; Pandey, A; Gurung, YB (Journal of BP Koirala Institute of Health Sciences, 2019)
Epidermoid cysts are rare benign neoplasm accounting for less than 1% of all intra-spinal tumors. Congenital epidermis cysts are frequently found with syringomyelia, dermal sinus and spina bifida. Most common etiology for an acquired cyst is repeated lumbar puncture. Congenital epidermoid cysts, often associated with other spinal dysraphisms, are caused by the anomalous implantation of ectodermalcells during closure of the neural tube between the third and fifth week of embryonic life. This is a very rare case. With all these characteristics and literature review, we report this case for its rarity and unique characteristics in this part of world (Nepal). These patients commonly present late to the hospital.